Study on the Influence of Moisture Content and Drying-Wetting Cycles on the Shear Strength Index of Silt in the West Bank of Qinghai Lake - Lei Zhang; Jixiang Yan; Jiake Tan; Yi Liao (Advances in Civil Engineering)
In this paper, the expressway engineering case along the west bank of Qinghai Lake is taken as the research background, and the typical “aquatic grassland” silt on the west bank of Qinghai Lake is taken as the research object. Through the geotechnical test, wet-dry cycle test, and direct shear test, the influence of moisture content and wet-dry cycle on the shear strength of silt and its indexes are studied. The results show that the shear strength index c and φ of unmodified silt first increase and then decline with the increase of water content, and the optimal moisture content of the shear strength is about 30%. The values of c, φ, and shear strength of remolded silt decrease with the increase of wetting and drying cycles. When the cycles exceed 5 times, the moisture content does not have much effect on the shearing strength.